Regenerative Endodontic Treatment in Dentinogenesis Imperfecta-Induced Apical Periodontitis - Ying Liao; Ting Pan; Xianghui Xing (Case Reports in Dentistry)
Pulp involvement of immature permanent teeth with dentinogenesis imperfecta is challenging and could lead to extraction. A case of dentinogenesis imperfecta-induced periapical periodontitis of an immature permanent tooth was treated with regenerative endodontic treatment (RET), and root maturation was observed in 12-month follow-up. An 8-year-old girl presented acute pain and swelling in central mandibular region. Clinical and radiographic examination revealed “shell teeth” appearance of teeth 31, 41, and 42. Periapical lesion of tooth 31 was observed. Tooth 41 was previously treated with apexification. RET was planned and carried out for the necrotic tooth (tooth 31) with dentinogenesis imperfecta. The 1-, 3-, 7-, and 12-month postoperative recall revealed complete healing of periapical lesions. Root maturation characterized by elongation of root, thickening of dentinal walls, and closure of root apex was observed with radiographic examinations. We show that RET could be a desirable treatment for necrotic immature permanent teeth with dentinogenesis imperfecta and lead to resolution of endodontic lesions as well as maturation of dental root. The findings of this case suggest that RET should be considered by endodontist and pediatric dentist to treat teeth with similar dental anomalies and apical periodontitis.